Protegiendo los derechos de propiedad intelectual y el conocimiento ecológico tradicional: una mirada crítica a la Ley 27811 del Perú - Hak Hepburn, Michelle L. (2021)
The Peruvian government’s Law N. 27811, an intellectual property law passed in 2002 and designed to register and protect tradItional knowledge, provides productive opportunities for critical analysis. Framed within the trajectory of international intellectual property rights and discussions that complicate the integration of Traditional Ecological Knowledge (TEK) into Cartesian scientific frameworks, this paper critically examines how the Peruvian law has been implemented and its impacts in Indigenous communities, particularly in the Andean Amazon region. The analysis is based on the author’s work assisting Indigenous communities in San Martin register their knowledge through this law. While the law represents an advanced legal attempt to address power inequalities, it remains problematic. It does not address the impoverishment of Indigenous Peoples and continues to subordinate Indigenous TEK to Cartesian science. Although it is a symbolic recognition of the value of Peruvian Indigenous Peoples, other mechanisms are still required to redress the long history of colonization and racism.